EFEKTIVITAS BLT DANA DESA DENGAN AKUNTABILITAS SEBAGAI PEMODERASI DI KABUPATEN ACEH TAMIANG - -, Athika Nuraliza Hanuma; Iqlima Azhar; Nasrul Kahfi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This research aims to determine the influence of human resource competence and community participation on the effectiveness of village fund BLT with accountability as a moderating variable. This type of research uses quantitative, the data source in this research uses primary data. The population and sample for this research are 16 villages in the Rantau sub-district. The samples taken in this research were 48 village fund BLT managers selected from each village in Rantau sub-district. This research uses a saturated sample, namely a sampling technique when the entire population is used as a sample. The data obtained was analyzed using SPSS (Statistical Package For Social Sciences) analysis techniques. The equation models analyzed are multiple linear regression analysis and Moderated Regression Analysis (MRA). The results of this research are: (1) Human resource competency has an influence significant to the effectiveness of village fund BLT, (2) Community participation has no significant effect on the effectiveness of village fund BLT,(3) Accountability has a significant effect on the effectiveness of village fund BLT, (4) Accountability can moderating the influence of human resource competence on BLT effectiveness village funds, (5) Accountability cannot moderate the influence of participation community towards the effectiveness of village fund BLT, (6) Simultaneous accountability or together they can moderate the influence of human resource competence and community participation in the effectiveness of fillage fund BLT. The limitation of this research is that it only used 48 respondents, which actually still does not describe the actual situation. Suggestions for future researchers are that they can add respondents and other independent variables such as budget participation variables.